Moringa (Moringa oleifera L.) Leaf Extract Gel Is Able to Reduce TNF-α and IL-6 Post Tooth Extraction in Male Wistar Rats (Rattus norvegicus) - Ni Putu Dian Cipta Dewi; I Made Jawi; Susy Purnawati (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Background: Tooth extraction is a procedure that can cause injury to the soft tissue. The inflammatory phase that occurs during wound healing triggers a series of tissue changes mediated by the immune system and cytokines. TNF-α and IL-6 cytokine levels should decrease as the wound heals, but otherwise it will slow wound healing and lead to chronic inflammation. The purpose of this study was to determine the effect of the extract gel of Moringa leaves on the wound healing process Materials and Methods: This research was conducted on 24 Wistar rats, which were randomly divided into four groups, 70%, 90% Moringa leaf extract gel group 70% and 90%, the control (+) oxyfresh gel, and the control (-) CMC-Na 2%. The left central incisor tooth was extracted, resulting in an injury to the gingival socket, and was given topical treatment every day for 7 days. Blood sampling from the orbital sinus was carried out on the 4th and 7th day after injury, and the levels of TNF-α and IL-6 were measured by ELISA. The data obtained was tested with two-way ANOVA and Post Hoc LSD. Results: The lowest IL-6 was found in the 90% Moringa leaf extract gel group, with an average of 80.86 ± 1.91, while the lowest TNF-α was found in the 90% day 7 group with 80.56 ± 0.41. There were significant differences between the test groups and the observation time, with p <0.05. Conclusion: Topical application of moringa oleifera gel was effective in reducing TNF-α.and.IL-6 levels after tooth extraction in Wistar rats